2004
DOI: 10.1002/eat.20056
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of illness in individuals with anorexia nervosa: A comparison with lay men and women

Abstract: The profile of illness perceptions expressed by the AN sample is associated with poor mental health and functioning and may inform the treatment approach. Lay perceptions of AN differed in the conceptualization of AN as a "slimming disease" amenable to change. This discrepancy may contribute to the stigmatization of AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
3
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 22 publications
(24 reference statements)
12
101
3
5
Order By: Relevance
“…This re-iterates the issue of inadequate mental health training for GPs (Copty & Whitford, 2005). However, it is worth noting that GPs ascribed patients the least personal control over their illness, which is consistent with the illness belief model held by those with AN themselves (Holliday et al 2005). This could promote a successful initial clinical consultation.…”
Section: Do Different Professional Groups Hold Different Beliefs Abousupporting
confidence: 53%
See 1 more Smart Citation
“…This re-iterates the issue of inadequate mental health training for GPs (Copty & Whitford, 2005). However, it is worth noting that GPs ascribed patients the least personal control over their illness, which is consistent with the illness belief model held by those with AN themselves (Holliday et al 2005). This could promote a successful initial clinical consultation.…”
Section: Do Different Professional Groups Hold Different Beliefs Abousupporting
confidence: 53%
“…This belief pattern is discrepant with Weinman et al's (1996) proposition that belief in the controllability and curability of an illness is associated with shorter perceived illness duration. In addition, the beliefs expressed by this professional sample are at odds with the illness models held by ED-affected individuals themselves, who tend to view their disorder as characterised by low controllability and curability (Holliday et al 2005). Discrepancies in the illness beliefs held by those affected and the people around them, including healthcare providers, are associated with psychological distress on the part of the patient (Quiles et al 2009).…”
Section: What Characterises Healthcare Professionals' Attitudes Towarmentioning
confidence: 95%
“…Finally, the measure has been examined in an eating disorder sample to assess their perception of the illness with good internal reliability. 44 …”
Section: Parent Measuresmentioning
confidence: 99%
“…Research showed that even physicians blame patients with AN for their eating disorder symptoms and associated behaviors [20]. Furthermore, the severity of AN is often underestimated by laypeople [21]. Consequently, as shown by research conducted with patients with depressive symptoms, stigmatization poses a major obstacle to seeking and attending therapy and treatment [14,22,23].…”
Section: Introductionmentioning
confidence: 99%